Challenges faced by International students at Kwantlen Polytechnic University (International Journal of Multidisciplinary Perspectives in Higher Education, 2019)
This study aimed to investigate the challenges international students face during their studies at Kwantlen polytechnic university. The research focused on the English language, study-related and financial issues, and adjustment to life in Canada. The participants were 25 females and 38 male students of 18- 35 years old from China, India and the Middle East. The materials included a challenges questionnaire, coping and religiosity scales, adjustment in Canada and religious involvement scales, and a demographic questionnaire. The data were collected at three campuses of KPU. The main challenges reported by the majority of international students were high tuition fees, high rents, part-time work, and missing the families. Most international students liked small class sizes, were satisfied with the education, felt comfortable communicating with professors, were welcomed by their peers and had adjusted to Canadian culture. In general, international students who used both emotion-avoidance and problem-focused coping strategies were better at facing challenges.